DAGUSIBU socialization at the Al–Ichsan Orphans and Dhuafa Foundation - Renny Amelia; Rinto Susilo; Yayan Rizkiyan; Ibnu Mas’ud; Arista Maulana; Hana Syifaun Nufus; Fathiyah Putri Alifia (Community Empowerment, 2022)
Public education on how to get, use, store, and dispose of drugs properly and correctly is still needed by the community. Many problems that occur in the community related to DAGUSIBU include choosing places that are not safe to get drugs, instructions for use that are not paid attention to, storage of drugs that are not according to instructions, and how to dispose of drugs that are not appropriate. The purpose of socialization is to provide information to students about how to get, use, store, and dispose of drugs properly and correctly. The results obtained after the socialization were the knowledge of the students about the importance of getting, using, storing, and disposing of drugs properly and correctly